Association between aerobic fitness and attentional functions in Egyptian preadolescent children - Abdelkarim, Osama; Aly, Mohamed; ElGyar, Noha; Shalaby, Amira M.; Kamijo, Keita; Woll, Alexander; Bös, Klaus (Frontiers in Psychology, 2023)
Growing evidence indicates that culture and education can influence cognitive constructs. Studies targeting Western and Asian populations have shown a positive relationship between aerobic fitness and cognitive control in children; however, this association has yet to be explored in the Arab world. The current study aimed to investigate the relationship between aerobic fitness and attentional networks in Egyptian preadolescent children. One hundred and three preadolescent children (9.76 ± 0.11) completed an assessment of aerobic fitness using a 6-minute running test and a computerized attention network test that allowed for assessing alerting, orienting, and executive networks. The results revealed that higher aerobic fitness was associated with shorter response time and higher response accuracy in a more cognitively demanding task condition (i.e., incongruent trials). Further, higher aerobic fitness was associated with a more efficient executive network. No associations were observed for alerting and orienting networks. These findings corroborate growing evidence indicating the importance of aerobic fitness for cognitive development and extend the literature by suggesting that the positive association between aerobic fitness and cognitive control might be generalized to the Arab population and not significantly change across cultures.